Nutritional, phytochemical, antioxidant activity and sensory attributes of herbal infusion from sukun (Artocarpus altilis) leaf - Azli, Siti Nur Shafiqah; Abu Bakar, Mohd Fadzelly; Sanusi, Shuaibu Babaji; Awang-Kanak, Fadzilah (2018)
“Sukun” or breadfruit, scientifically known as Artocarpus altilis contained several nutritive and pharmaceutical values. The objectives of this study were to determine the sensory attributes, phytochemicals, antioxidant activity, nutritional content, and physicochemical, of herbal tea prepared from A. altilis leaf at three different infusion temperatures (i.e. 45°C, 80 °C and 100°C). The samples were prepared by using hot water extraction method, and all extracts were later analysed for sensory attributes, phytochemical content, nutritional content, and also tested for antioxidant activity by using DPPH, FRAP, and ABTS assays. The sensory testing score where the highest score belonged to sample 357, infusion at 100°C with the score of 5.6±2.1, followed by sample 790, infusion at 80°C and 539, infusion at 45°C where both scored 4.9±1.9 and 4.2±2.1, respectively. Total phenolic (9.76±0.86) and total flavonoid (47.22±0.01) contents of A. altilis leaf tea was highest at 100°C of infusion temperature. As for antioxidant activity tests, the results demonstrated the same trend, that A. altilis leaf tea infused at 100°C of water displayed the highest antioxidant activity as for DPPH (8.84±0.04), FRAP (30.99±0.01), and ABTS (45.42±0.01) assays. Nutritional content for the highest infusion temperature (100°C) was 0.13% (carbohydrates), 0.1% (protein), 0.2% (fat), 0.04±0.01% (ash) and 99.53±0.23% (moisture content). Meanwhile, the concentration of sodium, calcium, potassium, and magnesium for that infusion was 0.34±0.03, 3.11±0.25, 1.18±0.05 and 0.81±0.06 mg/L, respectively. The physical properties were 0.66±0.01 for water activity, 0.2% total soluble solid and reading of color L*, a* and b* was 65.05±0.8, -0.87±0.08 and 20.66±0.1, respectively. As a conclusion, A. altilis dry leaf infused at 100°C displayed the highest antioxidant and phytochemicals properties and can be considered as functional food and nutraceutical.